Ekuilibrium Pengaturan Perlindungan Data Pribadi Sebagai Jaminan Hak Konstitusional: Refleksi Implementasi di Masa Pandemi Covid-19: The Equilibrium of Personal Data Protection Regulations as a Guarantee of Constitutional Rights: Reflections on Implementation during the Covid-19 Pandemic - Al Fikry, Ahmad Habib (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
Essence of the rule of law is the guarantee of human rights for every citizen. To dive deeper into this matter, the 1945 Constitution of the Republic of Indonesia, which is the constitution of the Indonesian state, contains a discussion in a special chapter, namely XA which regulates human rights. Human rights have various types, one of which is personal self-protection as regulated in Article 28G paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Personal protection is inherent with private rights which can include personal data of legal subjects. In line with the massive development of the world in the fields of technology, information, and communication, it has implications for the attachment of data subjects to the act of entering and transferring personal data in various kinds of activities. Data shows that there has been an increase in this activity during the pandemic covid-19. Personal data has become a topic of discussion when many data subjects are deprived of their rights to privacy, which can be seen in several cases of personal data leakage. For these problems, individuals need the protection of personal data as a concretization of the conception of the rule of law and guarantees of constitutional rights. The complexity of the problems that occur does not make the state remain silent. As a legal state that holds legal principles in its implementation, laws and regulations that contain the basic value of legal certainty are considered to be a solution. The seriousness of the state in overcoming this can be seen in the draft of the Personal Data Protection Law (RUU PDP), which is still being drafted by the Indonesian House of Representatives. This research, which uses a normative juridical method, discusses the protection of personal data as a right guaranteed by the constitution and its implementation during the pandemic covid-19. This paper aims to determine the suitability of the guarantee of constitutional rights and their implementation as well as to find an equilibrium in the regulation of personal data protection so that the full fulfillment of constitutional rights can occur.